Technologies of Interdisciplinary Approach in the Development of Eco–Steam Educational Competencies of Future Teachers - Yuldashovich, Kuchkinov Abdumalik (Researchparks Publishing, 2023)
In this article, environmental education for students, Eco–STEAM education is interdisciplinary and practical orientation of students, physics, biology, geography, informatics, technology, visual arts and engineering thinking, imagination, cooperation, creative abilities, formation of interdisciplinary environmental culture through independent education outside the classroom. thought about.